348 The New Normal? – a Survey of Patients' and Clinicians' Satisfaction of Remote Consultations During the COVID-19 Pandemic. (28th February 2022) - Byrne, H.; Roslan, F.; Kasbia, H.; Alzuri, H.; Kazi, S.; Sheikh, F.; Ahmed, J.
Abstract: Aim: Remote consultations (RC) were implemented during the COVID-19 pandemic with the aim of preventing transmission of the virus. We conducted a survey to assess patients' and clinicians' satisfaction of RC. Method: Two online surveys were created for patient and clinician feedback, and each recorded a cohorts' opinions on various aspects of RC. The surveys were distributed to Urology, General and Vascular surgery departments at three NHS trusts. Patient feedback was collected over the phone, whilst clinicians completed the survey online. Results: Overall, responses from 99 patients and 22 clinicians were collected. 89.9% of patients were either 'satisfied or very satisfied' with RC, compared to 77.2% of clinicians who practiced RC. 93.9 % of patients felt they were able to discuss all their concerns during their RC. However, outside of the COVID-19 setting 50% of patients and 59.1% of clinicians would prefer face to face consultations. Both cohorts reported adherence to social distancing and convenience as key advantages of RC; furthermore 68.2% of clinicians thought RC were economically beneficial. 100% of clinicians felt the inability to examine patients was a disadvantage of RC and 33.8% of patients agreed with this. Conclusions: The majority of feedback from patients and clinicians was positive for RC. However, in future approximately 55% of both cohorts would prefer face to face consultations. Looking forward, we believe RC can form a part of routine practice in selected groups of patients, where it could potentially save time and money without compromising patient or clinician satisfaction.